2020
DOI: 10.1155/2020/3091528
|View full text |Cite
|
Sign up to set email alerts
|

Observed Ground Pressure Acting on the Lining of a Large‐Diameter Shield Tunnel in Sandy Stratum under High Water Pressure

Abstract: Accurately evaluating the ground pressure on the tunnel lining greatly helps the structure design of a tunnel. In this study, the earth pressure and water pressure on the tunnel lining of four cross sections of a metro tunnel were measured and analyzed and then compared with the theoretical values. Results show that the values and distribution of observed ground pressure acting on the lining are different for different overburden depths. The water pressure measured on-site is approximately equal to the theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The theoretical solution for the deformation and stress of the proposed lining structure is provided based on the internal and external pressure elastic ring theory. To solve the problem that conventional double-layered linings can hardly meet the design requirements when facing high internal water pressure conditions, Wang (2018), Huang (2020), Lin (2020) proposed a novel three-layer lining structure composed of a shield pipe sheet, self-compacting concrete liner, and a steel sleeve structure. They explored the force-deformation behavior and load-bearing performance based on component tests and finite element numerical analysis.…”
Section: Ec 416 1640mentioning
confidence: 99%
“…The theoretical solution for the deformation and stress of the proposed lining structure is provided based on the internal and external pressure elastic ring theory. To solve the problem that conventional double-layered linings can hardly meet the design requirements when facing high internal water pressure conditions, Wang (2018), Huang (2020), Lin (2020) proposed a novel three-layer lining structure composed of a shield pipe sheet, self-compacting concrete liner, and a steel sleeve structure. They explored the force-deformation behavior and load-bearing performance based on component tests and finite element numerical analysis.…”
Section: Ec 416 1640mentioning
confidence: 99%
“…Permeation grouting is an effective geotechnical consolidation technique commonly employed to improve the mechanical behavior of sandy soils. The technique consists of the injection of chemical mixtures, with very low pressure, into the voids of porous natural soils [6,7]. Many scholars conducted the effect of fine sand reinforcement by different materials [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Rouhanifar Salman et al [18] studied the strength and deformation behavior of sand rubber mixtures by using the loose specimens with a void ratio of 0.86, corresponding to a relative density of 30% for the pure sand, and normal stresses of 50, 100, and 150 kPa. Xue Li et al [19] measured and analyzed the Earth pressure and water pressure on the tunnel lining of four cross-sections of a metro tunnel, then compared with the theoretical values, and found that the values and distribution of observed ground pressure acting on the lining are different for different overburden depths. Mingfeng Lei et al [20] proposed a heterogeneous equivalent beam model (HEB model) of the shield tunnel segment structure based on a systematical analysis of the stress state of the cross section of segment joints.…”
Section: Introductionmentioning
confidence: 99%